The Meaning Function of the Case Particle ʃi in the Tsuken Island Dialect of Japanese Considered from the Perspective of Collocative Relations - Matayoshi, Satomi (Slavia Centralis, 2020)
This paper describes the case particle ʃi in the Tsuken Island dialect of Okinawa, Japan. This particle has a similar function to the preposition to in the English language. It is thought that ʃi is equivalent to case particles ni or e in the Japanese standard language, but its origin is not clear. ʃi has not only the function of ni or e, but also one of the functions of Standard Japanese made. It seems that ʃi developed in the Tsuken Island dialect.